Chronotropic Incompetence and Cardiovascular Outcomes in Patients With Heart Failure With Preserved Ejection Fraction - Ting‐Tse Lin; Tzu‐Yang Chen; Jen‐Fang Cheng; Lian‐Yu Lin; Cho‐Kai Wu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Chronotropic incompetence is common in older people and contributes to heart failure with preserved ejection fraction (HFpEF). This prospective study investigated the impact of chronotropic incompetence on cardiovascular outcomes in patients with HFpEF. Methods and Results From November 2019 to December 2022, 359 subjects undergoing invasive cardiopulmonary exercise testing for heart failure symptoms were enrolled. After excluding those without HFpEF (resting pulmonary capillary wedge pressure <15 mm Hg or exercise pulmonary capillary wedge pressure <25 mm Hg), 113 patients were followed long term. Outcomes included hospitalization for HF and cardiovascular death. Associations between exercise hemodynamic parameters and outcomes were evaluated using Cox regression analysis. Among the 113 patients, 85 (75.2%) had chronotropic incompetence; these patients were older (71 versus 66 years) and more often female (61% versus 28%) compared with those without chronotropic incompetence. At peak exercise, patients with chronotropic incompetence exhibited lower left atrial (LA) booster strain, impaired right ventricle–arterial coupling, reduced systemic vascular resistance, cardiac output, stroke volume, peak oxygen consumption, and respiratory exchange ratio, along with a steeper minute ventilation/carbon dioxide production slope. They also had higher pulmonary capillary wedge pressure (36±10 versus 26±11mm Hg, P=0.012). Over a median follow‐up of 22.6 months, 20 patients (17.7%) experienced cardiovascular events. Multivariate analysis identified chronotropic incompetence (hazard ratio [HR], 1.725 [95% CI, 1.212–2.413]) and an elevated pulmonary capillary wedge pressure/cardiac output slope (HR, 1.829 [95% CI, 1.331–2.382]) as predictors of adverse outcomes. Conclusions In HFpEF, chronotropic incompetence is associated with elevated filling pressures, impaired ventilatory efficiency, and reduced exercise capacity, contributing to hospitalization for HF and cardiovascular death. Recognizing chronotropic incompetence may help predict poor prognosis in HFpEF.